Dimerization through the helix-loop-helix motif enhances phosphorylation of the transcription activation domains of myogenin. - Zhou, J (Mol Cell Biol, 1994)
The muscle-specific basic helix-loop-helix (bHLH) protein myogenin activates muscle transcription by binding to target sequences in muscle-specific promoters and enhancers as a heterodimer with ubiquitous bHLH proteins, such as the E2A gene products E12 and E47. We show that dimerization with E2A products potentiates phosphorylation of myogenin at sites within its amino- and carboxyl-terminal transcription activation domains. Phosphorylation of myogenin at these sites was mediated by the bHLH region of E2A products and was dependent on dimerization but not on DNA binding. Mutations of the dimerization-dependent phosphorylation sites resulted in enhanced transcriptional activity of myogenin, suggesting that their phosphorylation diminishes myogenin's transcriptional activity. The ability of E2A products to potentiate myogenin phosphorylation suggests that dimerization induces a conformational change in myogenin that unmasks otherwise cryptic phosphorylation sites or that E2A proteins recruit a kinase for which myogenin is a substrate. That phosphorylation of these dimerization-dependent sites diminished myogenin's transcriptional activity suggests that these sites are targets for a kinase that interferes with muscle-specific gene expression. IMAGES: